FEASIBILITY STUDY HOTEL DI BENGKALIS (STUDI KASUS HOTEL WISMA KITO BENGKALIS) - Muhammad Alkadri Perdana; Hutomo Atman Maulana (Inovbiz: Jurnal Inovasi Bisnis, 2018)
Investment in hotel business is a high-risk decision because it requires very large capital and aims to benefit in the future. To minimize risk and estimate the amount of profit to be obtained, a feasibility study of investment is needed. This study aims to find out the breakdown of the calculation of business investments made in hotels in Bengkalis Regency in detail. Feasibility Study is conducted to find out whether or not investment in hotel development in Bengkalis Regency is worthy. This feasibility study was carried out using the calculation of Break Even Point Analysis (BEP), Net Present Value (NPV), Pay Back Period Analysis and Internal Rate of Return (IRR). Research data collection was carried out through surveys, interviews and direct observation to the location. This study also uses secondary data from the Bengkalis Regency Central Statistics Agency. The results of this study show that Break Event Point (BEP) is 31 years 11 months 11 days, Net present Value (NPV) is Rp.2.536.661.016, and Internal Rate of Return (IRR) is 12,512%.